Viral replication organelles: the highly complex and programmed replication machinery - Deng, Hao; Cao, Hongwei; Wang, Yanjin; Li, Jiaqi; Dai, Jingwen; Li, Lian-Feng; Qiu, Hua-Ji; Li, Su (Frontiers in Microbiology, 2024)
Virus infections usually induce the rearrangement of cellular cytoskeletal proteins and organelle membrane structures, thus creating independent compartments (termed replication organelles (ROs)) to facilitate viral genome replication. Within the ROs, viral replicases, including polymerases, helicases, and ligases, play functional roles during viral replication. These viral replicases are pivotal in the virus life cycle, and numerous studies have demonstrated that the viral replicases could be the potential targets for drugs development. Here, we summarize primarily the key replicases within viral ROs and emphasize the advancements of antiviral drugs targeting crucial viral replicases, providing novel insights into the future development of antiviral strategies.